Ambiente de leitura, valores e atitudes como preditores de engajamento escolar e desempenho acadêmico - Maia, Analinne (2013)
This study is aimed to explain the school engagement and academic performance through the antecedent variables of the individual order (values and attitudes) and contextual (reading environment). This was a correlational research design, in which psychometric measures were considered ex post facto in nature. Counted with the participation of 350 students from 6th and 7th grade level, with 48.9% male and 51.1% female, ranging in age from 9 to 13 years (M = 11.13; SD = 0.70). The sample was characterized as a nonprobabilistic, that is, convenience. The participants answered a questionnaire Sociodemographic, checking sex, age, and average performance in math and Portuguese, the Environment Rating Scale Reading (EAAL); School Engagement Scale (EES); Scale Attitudes Towards School ( EAE), and Basic Values Questionnaire - Child (QVB-I). Data analysis was performed by using the statistical package DMSS 21. To check the adequacy of the model, there was a path analysis (path analysis) to test the theoretical hypothesis proposed here, in which it was considered the covariance matrix and adopted the method of estimation (ADF Asymptotically Distribution-Free). The results demonstrated its suitability indicators the 2nd adjustment observed: χ ² / df = 3.18, GFI = 0.95, AGFI = 0.91, CFI = 0.94, RMR = 0.05 and RMSEA = 0.07 (90% CI = .06 to .09). In this study, it would be approved (M = 4.61, SD = 0.97), a higher score in factor dedication, a component of school engagement, compared to those who would not be approved (M = 4.35, SD = 1,25). According to the result of the research, reading environment is the variable that best predicts academic performance in relation to other variables as predictors proposals, demonstrating the influence of parental behavior as determinants for their children's behavior while environmental factor.